PENERAPAN PSAK NO. 50 (REVISI 2006) DAN PSAK NO.55 (REVISI 2006) PADA PT. BANK RIAU KEPRI CABANG PEMBANTU UJUNG BATU - Yuliza, Arma (E-Journal Cano Ekonomos, 2013)
PSAK No. 50 (Reviseing 2006) arranging about monetary instrument expression and presentation. PSAK No. 55 (Reviseing 2006) arranging about confession and measurement of monetary instrument. Matter which enough krusial from both the PSAK to bank is that credit as bank asset classified at